Asymptotic ruin probabilities of a two-dimensional renewal risk model with dependent inter-arrival times. Issue 7 (2nd April 2020) - Cheng, Dongya; Yu, Changjun
Abstract: This article mainly considers the uniform asymptotics for the finite-time ruin probabilities of a two-dimensional renewal risk model with heavy-tailed claims. In this model, the two claim-number processes are arbitrarily dependent and each of them is generated by widely orthant dependent claim inter-arrival times. Two types of ruin are studied and for each type of ruin, an asymptotic formula for the finite-time ruin probability is established. These formulae possess a certain uniformity feature in the time horizon.